1998
DOI: 10.1016/s0029-7844(97)00627-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Patient Reports of Urinary Incontinence Symptoms and Quality of Life Measures

Abstract: Primary care practitioners may screen for problematic incontinence by asking if patients' incontinence is bothersome to them and by obtaining simple historic information on voiding and leaking patterns. These questions may provide an efficient tool to detect bothersome incontinence in older women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 10 publications
2
50
0
2
Order By: Relevance
“…The QoL of women with UI is a¡ected by a number of factors. UI type has been shown to di¡erentially a¡ect QoL, and urge UI has been found to have a greater impact on QoL than stress UI Hunskaar and Vinsnes, 1991;Grimby Robinson et al, 1998]. Many other di¡erent factors (e.g., menopause, ageing, obesity, previous gynecologic operations, higher parity, vaginal delivery, jobs involving heavy lifting, and uterovaginal prolapse) have also been shown to in£uence the prevalence and severity of UI Mommsen and Foldspang, 1994;Meyer et al, 1998].…”
Section: Discussionmentioning
confidence: 99%
“…The QoL of women with UI is a¡ected by a number of factors. UI type has been shown to di¡erentially a¡ect QoL, and urge UI has been found to have a greater impact on QoL than stress UI Hunskaar and Vinsnes, 1991;Grimby Robinson et al, 1998]. Many other di¡erent factors (e.g., menopause, ageing, obesity, previous gynecologic operations, higher parity, vaginal delivery, jobs involving heavy lifting, and uterovaginal prolapse) have also been shown to in£uence the prevalence and severity of UI Mommsen and Foldspang, 1994;Meyer et al, 1998].…”
Section: Discussionmentioning
confidence: 99%
“…7 OAB with UUI ('wet OAB') appears to affect QoL more than dry OAB. 14,[19][20][21] Results of the European survey published by Irwin et al 14 showed that participants with wet OAB were significantly more likely than those with dry OAB to express worry about having accidents and concern about participating in activities away from home. Accordingly, the results of the NOBLE program showed that OAB patients presented higher symptom bother scores than controls, with wet OAB patients reporting a higher impact of symptoms on physical function, role limitation, vitality, general health perception, bodily pain, and social function.…”
Section: Socioeconomic Burden Quality Of Life and Social Impactmentioning
confidence: 99%
“…The symptomatic burden of OAB is significant, with symptoms disrupting daily activities, sleep, mental health, and personal relationships 4,5 . Furthermore, OAB symptoms have a negative impact on health-related quality-of-life (HRQoL) 4,6,7 , and there is evidence that comorbidities such as depression, fractures, skin infections, and urinary tract infections may be associated directly with OAB 8 . In the US, the cost of OAB was estimated to be $65.9 billion in 2010, with $49.1 billion of direct medical costs; this was projected to increase to $76.2 billion and $82.6 billion in 2015 and 2020, respectively 9 .…”
Section: Introductionmentioning
confidence: 99%